INTERVISTA A LAURA TASSINARI, DIRETTORE GENERALE FILAS - MediaGEO, Redazione (Archeomatica, 2013)
New technologies applied to cultural heritage can make visits tohistorical and archaeological sites in an exciting discovery throughstorytelling techniques that use all the paradigms of multimedia.One area where the development of innovative enterprises is importantto enhance the local economy.